Characteristics of Specific Fuel Consumption on Exhaust Emissions in Diesel Engines Fueled by B20 and B100 - Wiliandi Saputro; Jayan Sentanuhady; Willie Prasidha; Luluk Edahwati; Wahyu Dwi Lestari; Ndaru Adyono; Tria Puspa Sari; Ahmad Khairul Faizin; Radissa Dzaky Issafira (Nusantara Science and Technology Proceedings)
The dependence of Indonesian people on diesel fuel is still very high, proven by the increasing amount of diesel fuel consumption yearly. The increase in diesel fuel consumption is a severe problem that must be anticipated because diesel is a fuel that originates from fossils and is non-renewable. In addition to its limited availability, environmental issues are also a matter of concern in the use of diesel fuel because the resulting exhaust emissions can interfere with health and increase global warming. One way to overcome this is to switch from fossil fuels to biofuels, i.e., biodiesel. Although theoretically biodiesel can be used directly as a substitute for diesel fuel, there is very little research on the fuel consumption required for the exhaust emissions produced. Therefore this study aims to determine the correlation between the characteristics of specific fuel consumption (SFC) on exhaust emissions produced in diesel engines using B20 (20% biodiesel + 80% diesel) and B100 (100% biodiesel) fuel. Based on the results of the study, it was found that an increase in SFC resulted in a downward trend in carbon monoxide (CO) and carbon dioxide (CO2) emissions. In the meantime, the hydrocarbon (HC) emissions and the resulting smoke opacity increased; this was influenced by several factors such as an increase in combustion temperature, increased deposit, and component wear.